When cardiac tamponade puts the pressure on. Issue 2 (February 2017) - Kaplow, Roberta; Iyere, Karen
Abstract : Refresh your knowledge of this potentially life-threatening complication of cancer, cancer treatment, or both. For optimal patient outcomes, keep a high level of clinical suspicion to identify patients at risk, recognize signs and symptoms early, and provide therapeutic interventions and supportive therapies.